Potential of para-rubber production in Thailand: Production technology management, problems and suggestions for yield improvement - Buncha Somboonsuke; Chaiya Kongmanee; Narisa Thongtrai; Purawich Phitthayaphinant (My University, 2018)
Potential of para-rubber production in Thailand: Production technology management, problems and suggestions for yield improvementKasetsart Journal of Social Sciences -- formerly Kasetsart Journal (Social Sciences), Volume 039, Issue 1, January 2018- April 2018, Pages 645-659ISSN: 2452-3151(0125-8370)DOI: doi.org/10.34044/j.kjss.2018.39.1.05Buncha Somboonsukea,*, Chaiya Kongmaneeb, Narisa Thongtraic, Purawich Phitthayaphinantd Download11 Downloads, Cited by N/A aDepartment of Agricultural Development, Faculty of Natural Resources, Prince of Songkla University, Songkhla 90112, ThailandbDepartment of Agricultural Economics, Faculty of Economics, Prince of Songkla University, Songkhla 90112, ThailandcDepartment of Agricultural Development and Resource Management, Faculty of Agricultural Technology, King Mongkut's Institute of Technology Ladkrabang, Bangkok 10520, ThailanddFaculty of Technology and Community Department, Thaksin University, Phatthalung 93210, Thailand*Corresponding author, e-mail: buncha.s@psu.ac.th AbstractThe research described the socio-economic characteristics, production technology management and production problems of para-rubber farmers in Thailand, and provided suggestions for yield improvement. Primary data were collected using structured interviews from a sample size of 2,971 para-rubber farmers managed by the Office of the Rubber Replanting Aid Fund (ORRAF) in Thailand. Sampling used the multi-stage, random sampling technique. In addition, panel discussions were used for brainstorming of officers of the ORRAF and representatives of smallholding para-rubber farmers in Thailand. Descriptive statistics and manifest content analysis were used for data analysis. The results showed that para-rubber farmers in Thailand were late-middle-aged smallholders. The most popular grown para-rubber variety was RRIM 600. Para-rubber trees were tapped for an average of 144.25 days per year. The highest average dry rubber yield was in the western region (274.85 kilograms per rai per year). In contrast, the average dry rubber yield in the northern region was lowest (243.36 kilograms per rai per year). The key production problems of Thai para-rubber farmers were under-use of chemical fertilizers and tapping during inappropriate periods. Suggestions for yield improvement were to provide education regarding appropriate fertilizer application and to improve cost management with regard to para-rubber production for Thai para-rubber farmers. Keywordspara-rubber, para-rubber farmer, production technology Downloads
Keywords: Indian Economic and Social Development